2023
DOI: 10.3389/fgene.2023.1121018
|View full text |Cite
|
Sign up to set email alerts
|

Development of a risk model to predict prognosis in breast cancer based on cGAS-STING-related genes

Abstract: Background: Breast cancer (BRCA) is regarded as a lethal and aggressive cancer with increasing morbidity and mortality worldwide. cGAS-STING signaling regulates the crosstalk between tumor cells and immune cells in the tumor microenvironment (TME), emerging as an important DNA-damage mechanism. However, cGAS-STING-related genes (CSRGs) have rarely been investigated for their prognostic value in breast cancer patients.Methods: Our study aimed to construct a risk model to predict the survival and prognosis of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 96 publications
0
1
0
Order By: Relevance
“…Another way to evaluate STING activation would include assessment of downstream effector molecules. STING-related gene signatures were associated with prognosis in breast, prostate, and colorectal cancers ( 28 , 29 , 32 ). Therefore, developing alternative protein markers alongside STING could provide a more comprehensive understanding of STING activation and its functional implications even in cases when upstream signaling pathway is compromised by genetic alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Another way to evaluate STING activation would include assessment of downstream effector molecules. STING-related gene signatures were associated with prognosis in breast, prostate, and colorectal cancers ( 28 , 29 , 32 ). Therefore, developing alternative protein markers alongside STING could provide a more comprehensive understanding of STING activation and its functional implications even in cases when upstream signaling pathway is compromised by genetic alterations.…”
Section: Discussionmentioning
confidence: 99%
“…In HER2 breast cancers, POLR2K gain of expression by mRNA upregulation or gene amplification was observed [144]; more recent studies showed that low expression of POLR2K significantly prolonged patients survival and reduced cancer rates in breast cancer, while the high expression of POLR2K was associated with poor patients' survival [145]. Recently, along with four other genes, higher POLR2K expression levels were found via machine learning approaches in a high-risk group of patients for breast cancer [146]. Using mRNA expression profiling, POLR2K was firstly identified in 2016 as a differentially expressed gene in prostate cancer tissues compared to normal tissues, and later, it was evident that POLR2K differential expression had a significant prognostic value for patients overall survival [147,148].…”
Section: Polr2k/rpb12mentioning
confidence: 99%